Outcomes of Critically Ill Lung Cancer Patients Initiating Targeted Therapy or Immunotherapy in the Intensive Care Unit: A Single-Center Report. (August 2022) - Lazar Neto, Felippe; Sousa, Luana G.; Lewis, Whitney E.; Glisson, Bonnie; Heymach, John V.; Tsao, Anne S.; Ferrarotto, Renata
Introduction: Targeted therapy and immune checkpoint inhibitors (ICI) have drastically improved outcomes of metastatic non-small cell lung cancer (NSCLC) patients in outpatient settings. Because trials on critically ill patients are improbable, little is known about their efficacy among patients admitted to intensive care units (ICU).Methods: We retrospectively analyzed the clinical outcomes of critically-ill NSCLC patients receiving either ICI or targeted therapy during ICU admission at the MD Anderson Cancer Center from April 2016 to August 2020. We collected data on ICU admission diagnoses, sequential organ failure assessment (SOFA), previous cancer therapies, tumor gene mutations or translocations, and PD-L1 expression. Overall survival (OS) was calculated from the date of drug initiation using the Kaplan-Meier method.Results: Of 9898 ICU admissions, 9 patients with metastatic NSCLC who received either targeted therapy (5) or PD-1 ICI (4) during ICU admission were included. The most common reasons for ICU admissions were tumor visceral crisis (3/9) and sepsis (3/9). The median (range) admission SOFA was 4 (2-11). Six patients were naïve to systemic therapy. Five patients required mechanical ventilation. The median OS was 77 days (95%CI, 36-NA), and 5 patients were discharged alive (all received targeted therapy). The median OS of patients who received ICI was 25.5 days (95%CI, 8-NA) and for those who received targeted therapy was 218 days (95%CI, 77-NA). At 6 and 12 months follow-up, 3 and 2 patients who received targeted therapy were still alive, respectively.Conclusions: Our exploratory findings indicate a possible benefit of targeted therapy but suggest a lack of clinical utility of PD-1 ICI for critically ill metastatic NSCLC patients. Because of the small sample size, further studies are needed to expand on this topic.